Obesitas dengan Kanker Kolorektal, Bagaimana Keterkaitan Keduanya? - Balatif, Ridwan; Lubis, Nenni Dwi Aprianti (SCRIPTA SCORE Scientific Medical Journal, 2021)
Background: Obesity is still a frequent health problem. This condition of obesity has even increased both globally and nationally. It is feared that the increase in obesity cases will increase other disease conditions such as colorectal cancer. Objectives: This article will provide an overview of the relationship between obesity and the incidence of colorectal cancer so as to provide a current, easy-to-understand picture of obesity and colorectal cancer. Methods: This article was written using the literature search method. Sources of information are taken from E-books, websites, and search engines. Information taken in the period 2013-2020. Discussion: It is suspected that obesity through a chronic inflammatory process will cause cell DNA damage so that it is at risk of triggering cancer. Until now, there are 13 types of cancer that are closely related to the incidence of obesity. This condition of obesity in addition to increasing a person's risk of developing colorectal cancer, it can also increase the risk of death in obese individuals with colorectal cancer. Conclusion: Obesity condition increases the risk of incidence and mortality of colorectal cancer cases. Keywords: cancer, literature searching, obesity Â  Latar Belakang: Obesitas sampai saat ini masih menjadi permasalahan kesehatan yang sering terjadi. Kondisi obesitas ini bahkan mengalami peningkatan baik secara global maupun nasional. Peningkatan kasus obesitas ini dikhawatirkan akan meningkatkan kondisi penyakit lain seperti kanker kolorektal. Tujuan: Artikel ini akan memberikan pemaparan mengenai kaitan obesitas dengan kejadian kanker kolorektal sehingga dapat memberikan gambaran terkini yang mudah dipahami mengenai obesitas dan kanker kolorektal. Metode: Artikel ini ditulis dengan menggunakan metode pencarian literatur. Sumber informasi diambil dari E-book, website, dan search engine. Informasi yang diambil dalam rentang tahun 2013-2020. Pembahasan: Diduga obesitas dengan melalui proses inflamasi kronik akan mengakibatkan kerusakan DNA sel sehingga berisiko mencetuskan kanker. Sampai saat ini terdapat 13 jenis kanker yang berkaitan erat dengan kejadian obesitas. Kondisi obesitas ini selain akan meningkatkan risiko seseorang untuk mengalami kanker kolorektal, juga dapat meningkatkan risiko kematian pada individu yang mengalami kanker kolorektal dengan obesitas. Kesimpulan: Kondisi obesitas meningkatkanÂ  risiko kejadian dan mortalitas kasus kanker kolorektal. Kata Kunci: kanker, obesitas, pencarian literatur